Effect of Gaviscon Infant on gastro-oesophageal reflux in infants assessed by combined intraluminal impedance/pH. Issue 5 (25th April 2005) - Del Buono, R; Wenzl, T G; Ball, G; Keady, S; Thomson, M
Abstract : Background: Gaviscon Infant (GI) has been recommended for gastro-oesophageal reflux (GOR) in infants. Its efficacy has not been examined with a physiologically appropriate denominator to define the degree of GOR. Aim: To investigate the influence of Gaviscon Infant on GOR in infants using combined pH and intraluminal impedance measurement. Methods: Twenty infants (mean age 163.5 days, range 34–319 days) exclusively bottle fed, with symptoms clinically suggestive of GOR, underwent 24 hour studies of intra-oesophageal 6 channel impedance and dual channel pH monitoring, during which six random administrations (3+3) of Gaviscon Infant (625 mg in 225 ml milk) or placebo (mannitol and Solvito N, 625 mg in 225 ml milk) were given in a double blind fashion. Impedance/pH reflux data were recorded and analysed blind by one observer. Results: The median number of reflux events/hour (1.58 v 1.68), acid reflux events/hour (0.26 v 0.43), minimum distal or proximal pH, total acid clearance time per hour (time with pH below pH 4), and total reflux duration per hour were not significantly different after GI than after placebo. Reflux height was marginally lower after GI (median 66.6% v 77.3% oesophageal length) compared with placebo. Conclusions: Results showed a marginal but significant difference between Gaviscon Infant and placebo in average reflux height, and raises questions regarding any perceived clinical benefit of its use.